Effect of Nursing Exercise Protocol on Hemodynamics and Functional Capacity among Patients after Cardiac Surgery - Asmaa A. A. Mohamed; Manal S. Hassan; Yasser S. M. Mubarak; Lobna M. Gamal (Evidence-Based Nursing Research)
Context: Exercise interventions are the cornerstone of cardiac rehabilitation. The exercise program consists of respiratory physiotherapy, neck and shoulder exercises, walking, and cycling. The purpose is preventing respiratory complications, neck and shoulder pain, and increasing the physical functional level.